20-Week Study of Clinical Outcomes of Over-the-Counter COVID-19 Prophylaxis and Treatment - Leon Margolin MD, PhD; Jeremy Luchins PhD; Daniel Margolin Bsc; Michelle Margolin; Sanford Lefkowitz MSc (SAGE Publishing, 2021)
Objectives and Setting. As the lethal COVID-19 pandemic enters its second year, the need for effective modalities of alleviation remains urgent. This includes modalities that can readily be used by the public to reduce disease spread and severity. Such preventive measures and early-stage treatments may temper the immediacy of demand for advanced anti-COVID measures (drugs, antibodies, vaccines) and help relieve strain also on other health system resources. Design and Participants. We present results of a clinical study with a multi-component OTC "core formulation" regimen used in a multiply exposed adult population. Analysis of clinical outcome data from our sample of over 100 subjects − comprised of roughly equal sized regimen-compliant (test) and non-compliant (control) groups meeting equivalent inclusion criteria − demonstrates a strong statistical significance in favor of use of the core formulations. Results. While both groups were moderate in size, the difference between them in outcomes over the 20-week study period was large and stark: Just under 4% of the compliant test group presented flu-like symptoms, but none of the test group was COVID-positive; whereas 20% of the non-compliant control group presented flu-like symptoms, three-quarters of whom (15% overall of the control group) were COVID-positive. Conclusions. Offering a low cost, readily implemented anti-viral approach, the study regimen may serve, at the least, as a stopgap modality and, perhaps, as a useful tool in combatting the pandemic.